Splenotoxic effect of radiographic developer effluent on Wistar rats - Ugwu, Anthony C.; Dimkpa, Uchechukwu; Agba, Obianuju N.; Eteudo, Albert N.; Anikeh, Livinus C.; Maduka, Stephen O.; Uchefuna, Roy C.; Njoku-Oji, Nancy N.; Okonkwo, Onyeka C. (International Journal of Research in Medical Sciences, 2016)
Background: Histological changes associated with toxicity of radiographic developer effluents on spleen tissues have not been previously studied. The present study therefore aimed at demonstrating the histopathological changes in splenic tissues of Wistar rats following exposure to developer effluent. Methods: Eighteen young Wistar rats weighing 140-220g were used for the study. The animals were divided randomly into three groups of 6 rats each based on the dose of developer effluent administered to them – i.e. control group I (0 dose) and experimental groups II (lower dose, 200 mg/kg) and III (higher dose, 400 mg/kg) respectively. The groups were further classified as either A or B sub-groups of three rats each, depending on the duration (14 or 28 days) of effluent administration. The effluent administration was done by oral gavages. Results: Normal spleen histology was observed in the control group. In contrast, tissue degeneration and necrosis; lymphocytic infiltration as well as reduction of splenic follicles were observed in some of the test groups (IIA, IIB and IIIA). Interestingly, the toxic effects of the developer effluent on group IIIB administered with higher dose for a longer period of 28 days were not as severe as observed in the other test groups. Conclusions: The present study which indicated adverse effects of exposures to sub-lethal doses of developer effluent on Wistar rats’ spleen tissues suggests the need for proper management and disposal of radiographic effluents.